Learning to suck eggs, or is there a case for a postgraduate development studies benchmark? - Copestake, James (2002)
Many academic disciplines in the UK have recently introduced subject benchmarks that specify core or minimum content for particular degrees. The article suggests that efficiency, quality, and transparency arguments in favour of such benchmarks may be undermined by problems in specification, identification, and implementation. By contrasting the programme specification for the Master's in development studies at Bath (overspecified) with the benchmark for Master's in management and business administration (underspecified), it suggests that an intermediate benchmark for development studies could usefully enhance transparency about what development studies is and what it has to offer.- Reproduced. ley & Sons, Ltd. - Reproduced.
Keywords: Development education